MENINGKATKAN KEMAMPUAN MENULIS KARANGAN NARASI DENGAN MENGGUNAKAN MULTIMEDIA - Ahmad Asrul Nasution (Universitas Negeri Medan, 2012)
The use of multimedia to create creativity, fun and not boring, to train children to think logically, to develop students' ideas, helping children to understand the problem easily and quickly. Multimedia is media that involves several types of media to stimulate all the senses in the learning activities. Media is designed to address students 'difficulty in understanding a problem and can improve students' ability to understand the abstract concepts more easily. These criteria will help the students to remember the concept of writing essays and narrative elements that are learning less attractive to them. Therefore, the ability of students to write a narrative essay can be improved through the use of multimedia learning. Keywords: Multimedia-Improve-Ability-Writing-Narrative